Antitrust Law Analysis on the Abuse of Dominant Position in Franchise Agreements in Indonesia - Kennedy, Alexander; Astea Novtalia Liuman; Natallia Lai; Stefanie Claudia Abdi Muljo (Journal of Legal and Cultural Analytics, 2025)
This study examines the abuse of dominant positions in franchise agreements in Indonesia, highlighting power imbalances between franchisors and franchisees and their impact on market fairness, competition, and franchisee autonomy. Employing a normative juridical methodology, the research analyzes legal frameworks, including Law No. 5 of 1999 on Monopolistic Practices, complemented by comparative studies of international practices. The findings reveal gaps in Indonesia's regulations, enforcement challenges, and significant power asymmetries in franchising, underscoring the need for a dedicated regulatory framework, enhanced institutional capacity, and stakeholder engagement. Recommendations include adopting a Franchise Disclosure Document, dispute resolution mechanisms, and fostering local franchise growth.